Risk factors of coronary artery disease in 27425 outpatients - A. S. Galyavich; R. N. Khairullin; L. V. Baleeva; M. Sluiter; S. V. Akimova; A. F. Galimzyanov; D. D. Aminov; D. D. Safin; A. Yu. Vafin; P. Terpstra (Российский кардиологический журнал, 2019)
Aim. To identify risk factors in outpatients without signs of coronary artery disease (CAD).Material and methods. The Portavita computer program adapted to Russian conditions was used. Information was collected and entered into the module by district doctors and general practitioners during outpatient visits. The program involved 9 clinics, 406 district doctors and general practitioners. Individual data on sex, age, family history of CAD, smoking, physical activity, blood pressure, cholesterol level, creatinine (with the calculation of the glomerular filtration rate) and blood plasma glucose were made. Next, the system determined the risk of death from CAD according to the SCORE scale. In total, the data were entered by 27425 citizens aged 18 to 80 years old who have no obvious signs of CAD. Based on the data obtained, the program selected individual preventive measures for each patient. Then, on the basis of the initial data, the date of the next examination of each patient was planned. Results. In the group of people without CAD (27425 people blood pressure of more than 140/90 mm Hg was detected in 66,2% of patients, body mass index more than 30 kg/m2 — in 23% of patients, the level of total blood plasma cholesterol more than 5,2 mmol/l — in 68% of patients (including more than 8 mmol/l — in 874 people), plasma glucose levels of more than 6,1 mmol/l — in 13% of patients. On the SCORE  risk scale, data were calculated for 22907 people, while more than 10 points were found in 7% of the subjects.Conclusion. In ambulatory patients with no signs of CAD, arterial hypertension (66,2%) and total blood plasma cholesterol of more than 5,2 mmol/l (68%) are the most frequently recorded risk factors. The combination of two risk factors (arterial hypertension + total blood plasma cholesterol more than 5,2 mmol/l) is recorded regardless of age (younger than 60 years and older than 60 years) — in cases of 61,8% and 64,2%, respectively.